The Aging and Developmental Disabilities Networks: Can the Silos Be Dismantled? - Kaye, Lenard; Zeph, Lucille; Cobo-Lewis, Alan (Maine Policy Review, 2015)
The authors discuss the service networks for aging and developmental and physical disabilities, which have traditionally functioned in distinctly separate camps. They present the case for greater crossover between these networks and endorse increased alignment of the aging and disability networks in all arenas, including policy making, program development, education, and research.
Keywords: aging; developmental disabilities; service networks; Maine